Updates on Software Usability - Castro, Laura M. (IntechOpen, 2023)
Updates on Software Usability is a collection of high-quality contributions for developers and non-developers alike. Beyond the preliminaries, the book is organized into two other parts: "Designing for Usability" and "Testing for Usability". The chapters in the second section, "Designing for Usability", offer valuable insights and practical guidance to take into account during the early stages of product conception and development. On the other hand, the chapters in the third section, "Testing for Usability", reflect and formalize software usability's evaluation and validation processes. These two complementary views on the subject make this book a balanced and comprehensive volume, which the reader will undoubtedly find both interesting and useful.